A novel locus conferring resistance to Puccinia hordei maps to the genomic region corresponding to Rph14 on barley chromosome 2HS - Mehnaz, Mehnaz; Dracatos, Peter M.; Dinh, Hoan X.; Forrest, Kerrie; Rouse, Matthew N.; Park, Robert F.; Singh, Davinder (Frontiers in Plant Science, 2022)
Barley leaf rust (BLR), caused by Puccinia hordei, is best controlled through genetic resistance. An efficient resistance breeding program prioritizes the need to identify, characterize, and map new sources of resistance as well as understanding the effectiveness, structure, and function of resistance genes. In this study, three mapping populations were developed by crossing Israelian barley lines ‘AGG 396’, ‘AGG397’ and ‘AGG 403’ (carrying unknown leaf rust resistance) with a susceptible variety Gus to characterize and map resistance. Genetic analysis of phenotypic data from rust testing F3s with a P. hordei pathotype 5457 P+ revealed monogenic inheritance in all three populations. Targeted genotype-by-sequencing of the three populations detected marker trait associations in the same genomic region on the short arm of chromosome 2H between 39-57 Mb (AGG-396/Gus), 44-64 Mb (AGG-397/Gus) and 31-58 Mb (AGG-403/Gus), suggesting that the resistance in all three lines is likely conferred by the same locus (tentatively designated RphAGG396). Two KASP (Kompetitive allele-specific PCR) markers, HvGBSv2-902 and HvGBSv2-932, defined a genetic distance of 3.8 cM proximal and 7.1 cM distal to RphAGG396, respectively. To increase the marker density at the RphAGG396 locus, 75 CAPS markers were designed between two flanking markers. Integration of marker data resulted in the identification of two critical recombinants and mapping RphAGG396 between markers- Mloc-28 (40.75 Mb) and Mloc-41 (41.92 Mb) narrowing the physical window to 1.17 Mb based on the Morex v2.0 reference genome assembly. To enhance map resolution, 600 F2s were genotyped with markers- Mloc-28 and Mloc-41 and nine recombinants were identified, placing the gene at a genetic distance of 0.5 and 0.2 cM between the two markers, respectively. Two annotated NLR (nucleotide-binding domain leucine-rich repeat) genes (r2.2HG0093020 and r2.2HG0093030) were identified as the best candidates for RphAGG396. A closely linked marker was developed for RphAGG396 that can be used for marker assisted selection.